HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN TEKANAN DARAH PADA LANSIA DI PUSKESMAS MELONG ASIH CIMAHI - Somantri, Budi (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2015)
Background. Aging is a natural process after the three stages of life, namely children, adulthood and old age that cannot be avoided by any individual. The increase of the age will cause changes in the structure and physiological properties of a range of cells, organs and systems in the body. Metabolic processes that decrease on the elderly will lead to obesity due to decreased physical activity, then the excess calories will be converted into fat resulting in obesity. Overweight or obesity is one of the factors that can influence blood pressure and the development of hypertension. Purpose. The purpose of this research was to know the correlation between Body Mass Index with elderly blood pressure in puskesmas Melong Asih Cimahi. Methods. The methods in this study used analytic research method with cross sectional approach, there were 80 elderly (60- 74 years) as respondents. Sampling techniques used simple random sampling. Results. The results of univariat analysis used frequency distribution showed distribution evenly on IMT skinny (20%), normal (26.2%), fat (26.2%), obesity (27.6%). Similarly, on the frequency distribution of blood pressure normal (36.2%), pre hypertension (31.2%), and hypertension (32.6%). The results of Chi-Square statistical test showed p value = 0.000 a 0.05. Conclusions. The conclusions from this study which conducted on June 2013 that there was a correlation between Body Mass Index (BMI) with elderly blood pressure in Puskesmas Melong Asih Cimahi.